Interfacial segregation induced by severe plastic deformation in a Mg–Zn–Y alloy. (November 2016) - Basha, Dudekula Althaf; Sahara, Ryoji; Somekawa, Hidetoshi; Rosalie, Julian M.; Singh, Alok; Tsuchiya, Koichi
Abstract: For the first time, we report here segregation of Zn atoms to twin boundaries formed under 9% compression at room temperature (RT) in a Mg-3Zn-0.5Y (in at%) alloy. The wrought processed (textured) alloy was severely plastically deformed (SPD) through high pressure torsion (HPT) at RT. Zn segregation (2 to 4 at%) was observed on newly formed boundaries, such as twin boundaries (formed on compression only in HPT), low angle boundaries formed by deformation and grain boundaries due to recrystallization. First principles calculations performed on low angle boundaries shows that Zn atom prefers to segregate to the dislocations in the boundary. Graphical abstract: